The effect of grinding on the mechanical behavior of Y-TZP ceramics: A systematic review and meta-analyses. (October 2016) - Pereira, G.K.R.; Fraga, S.; Montagner, A.F.; Soares, F.Z.M.; Kleverlaan, C.J.; Valandro, L.F.
Abstract: The aim of this study was to systematically review the literature to assess the effect of grinding on the mechanical properties, structural stability and superficial characteristics of Y-TZP ceramics. The MEDLINE via PubMed and Web of Science (ISI – Web of Knowledge) electronic databases were searched with included peer-reviewed publications in English language and with no publication year limit. From 342 potentially eligible studies, 73 were selected for full-text analysis, 30 were included in the systematic review with 20 considered in the meta-analysis. Two reviewers independently selected the studies, extracted the data, and assessed the risk of bias. Statistical analyses were performed using RevMan 5.1, with random effects model, at a significance level of 0.05. A descriptive analysis considering phase transformation, Y-TZP grain size, Vickers hardness, residual stress and aging of all included studies were executed. Four outcomes were considered in the meta-analyses (factor: grinding x as-sintered) in global and subgroups analyses (grinding tool, grit-size and cooling) for flexural strength and roughness (Ra) data. A significant difference ( p <0.05) was observed in the global analysis for strength, favoring as-sintered; subgroup analyses revealed that different parameters lead to different effects on strength. In the global analysis for roughness, a significant difference ( p <0.05) was observed between conditions, favoring grinding; subgroup analyses revealed that different parameters also lead to different effects on roughness. High heterogeneity was found in some comparisons. Generally grinding promotes decrease in strength and increase in roughness of Y-TZP ceramics. However, the use of a grinding tool that allows greater accuracy of the movement (i.e. contra angle hand-pieces coupled to slowspeed turbines), small grit size (<50 μm) and the use of plenty coolant seem to be the main factors to decrease the defect introduction and allow the occurrence of the toughening transformation mechanism, decreasing the risk of deleterious impact on Y-TZP mechanical properties.